2010
DOI: 10.1177/1744987110364572
|View full text |Cite
|
Sign up to set email alerts
|

The challenges facing healthcare lecturers and professors to lead and promote a research-based culture for practice

Abstract: A qualitative study was undertaken to explore lecturers' and professors' views of their role in shaping attitudes to, and careers in, research for the nursing and allied health professional workforce. A purposive sample was used to identify key participants (n ¼ 30), from four universities across southwest England, with 7-8 participants from each institution. Data were collected between October 2005 and January 2007. Data were managed, analysed and coded with the assistance of the qualitative data analysis sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The present study also indicated that Research supervision (RS) was one of the most significant needs for enhancing the clinical nurses' research skills, management and organisation of research activities, which is supported by previous studies (Girot , Jamerson & Vermeersch , Severinsson ). The clinical nurses' right to receive effective research supervision and research education is of importance to enhance research confidence and participation (Severinsson ) in order to implement strategies that improve the level of quality in practice (Jasper , Kramer et al .…”
Section: Discussionsupporting
confidence: 89%
“…The present study also indicated that Research supervision (RS) was one of the most significant needs for enhancing the clinical nurses' research skills, management and organisation of research activities, which is supported by previous studies (Girot , Jamerson & Vermeersch , Severinsson ). The clinical nurses' right to receive effective research supervision and research education is of importance to enhance research confidence and participation (Severinsson ) in order to implement strategies that improve the level of quality in practice (Jasper , Kramer et al .…”
Section: Discussionsupporting
confidence: 89%
“…Research supervision is perhaps the most influential initiative to improve clinical nurses' research skills, management, and organization of research activities (Girot, ; Akerjordet et al ., ; Jamerson & Vermeersch, ; Severinsson, ). Engaging subsets of clinical nurses who highly value nursing research to participate in a collaborative clinical–academic research network is a better strategy for research utilization than focusing on barriers (Brown et al ., ; Jamerson & Vermeersch, ).…”
Section: Discussionmentioning
confidence: 99%
“…Education is necessary to enable nurses to participate in and use evidence‐based clinical research. Girot () suggested employing professors who are leaders in their fields to promote a research‐based culture in clinical practice and engagement in research activity, as well as to support dissemination and provide research leadership.…”
Section: Discussionmentioning
confidence: 99%